The Role of Industry 5.0 in Advancing AI-Driven Predictive Analytics in Business Operations - Mihalj Bakator, Dragan Cockalo and Milan Nikolic (My University, 2024)
This paper analyzes the synergistic integration of AI-driven predictive analytics within Industry 5.0, emphasizing its transformative impact on business operations across various sectors. It highlights the role of artificial intelligence in enhancing human-machine collaboration to create more responsive, sustainable, and personalized manufacturing environments. Through detailed analysis, the paper notes how AI not only optimizes operational efficiencies but also enables the personalization of products and services, thus meeting diverse consumer needs with unprecedented precision. The study proposes a theoretical model comprising three main elements: the enterprise, AI-driven predictive analytics, and the enterprise in Industry 5.0. The paper offers comprehensive strategies for governments, enterprises, and individuals to improve problem-solving and foster innovation within the rapidly evolving industrial landscape.
Keywords: Industry 5.0; AI solutions; Predictive analytics; Business